The P3 Reflects Awareness and Can Be Modulated by Confidence - Ye, Muwang; Lyu, Yong; Sclodnick, Ben; Sun, Hong-Jin (Frontiers in Neuroscience, 2019)
An important question in neural correlate of consciousness (NCC) studies is whether event-related potential (ERP) component P3 reflects visual awareness or the confidence with which one reports a visual experience. In the present study, participants detected visual stimuli presented at threshold-level contrast, then rated their subjective confidence with respect to their response on a four-point scale (very confident, quite confident, slightly confident, and not confident at all). Because awareness responses in trials with rating of “not confident at all” were likely noise, we analyzed the data excluding those trials. The ERP results revealed a significant positive difference in P3 amplitude between “aware” and “unaware” trials. P3 amplitude was more positive in aware trials compared to unaware trials. Importantly, this pattern was observed for trials with combined confidence ratings of “very confident” and “quite confident”, and for trials with confidence ratings of “slightly confident”, suggesting that awareness alone can modulate P3. A significant interaction between awareness and confidence is reported, suggesting that confidence influences P3 as well. In addition, ERP results revealed that visual awareness negativity (VAN) was observed over posterior temporal and occipital electrodes and largely not influenced by confidence. This result indicated that VAN is an early neural correlate of visual awareness.